VALUES ACTUALIZATION IN THE EDUCATIONAL PROCESS - Lidaka, Anita; Samusevica, Alida; Striguna, Santa (European Scientific Journal, ESJ, 2013)
The person’s value is the choice he or she makes between a number of competing alternatives, thus defining what is important in his or her life. Values are the way a person communicates to other people, putting oneself along with them or against them. Values can be understood only in the context of other people and other values. They explain human behaviour and choices much better than leisure, socio-demographic characteristics or consumption of themes. Values are the criteria for decisionmaking in situations where there are limitations - and they exist in almost every moment of our lives - they can be time, money, abilities, and various other constraints. Each person’s future as well as national achievements of Latvia and preservation of national culture is dependent on the population education level, education quality and those capacities that help people find their place in life and professional fulfilment. All parents share one single desire for their children to find their place in life and become happy. In the majority of Latvian society the prevailing opinion is that due to obtained good quality education a person can significantly influence his own life, change the existing social status and develop prosperity. Throughout times education has been a fundamental value in Latvia. Just because of that in the process of the younger generation development it is very essential to pay attention to the promotion of the values’ formation. It is therefore very important for students to discover the importance of different values in the educational process.